Profiles of Work and Quality of Life among Young Adult Cancer Survivors. (April 2023) - Ghazal, Lauren V.; Merriman, John D.; Santacroce, Sheila J.; Fletcher, Jason; Wright, Fay; Dickson, Victoria Vaughan
Work ability, or the perception of one's ability to work presently and in the future, may impact quality of life (QOL) among young adult (YA) cancer survivors. Through a convergent mixed methods design, we explored work ability, work-related goals, and QOL among YA hematologic cancer survivors within five years of diagnosis. We described associations at the individual- and microsystem (work)- levels; and compared factors across low and high work ability groups. Participants ( N  = 40) completed a survey and interview via digital platforms. Qualitative analysis revealed self-assessed declines in work ability led to questioning work-related goals and influenced QOL. Integrated analysis led to the development of four profiles, growing our understanding of work's influence on QOL for YA cancer survivors, and identifying components YAs considered when contemplating work-related goals after a cancer diagnosis. Larger studies are needed to elucidate these profiles and identify modifiable factors to inform targeted interventions to improve QOL.